Impact strength of hybrid woven sugar palm fibre reinforced unsaturated polyester composites - Misri, Sairizal (2009)
In recent years, sugar palm fibre has been found to have great potential to be used as fibre reinforcement in polymer matrix composites. This research investigates the impact strength of woven sugar palm/glass fibre reinforced unsaturated polyester hybrid composite. The composite specimens made of different layer of fibres such as strand mat and natural woven sugar palm fibres. The composites were fabricated using a compression moulding technique. The impact test was carried out in accordance to ASTM D256 standard. The results of the experiment showed that the impact strength of hybrid composite was higher than natural woven sugar palm fibre. As a conclusion, the usage of glass fibre had improved the impact properties of sugar palm fibre composites.